Who Favors al-Qaeda? Anti-Americanism, Religious Outlooks, and Favorable Attitudes toward Terrorist Organizations. (September 2017) - Ciftci, Sabri; O'Donnell, Becky J.; Tanner, Allison
This study examines why ordinary people sympathize with a terrorist network in the Middle East and North Africa (MENA). Holding literalist religious outlook resonating with al-Qaeda's marginal interpretation of Islam constant, it is maintained that anti-Americanism and its varieties matter a great deal in explaining attitudes toward al-Qaeda. Using Pew Global Attitudes Surveys conducted in Turkey, Egypt, Jordan, and Tunisia, the authors run conditional mixed process estimations combining seemingly unrelated regressions with selection models to account for the missing values and endogeneity problems. The analysis reveals significant variation both cross-nationally and in the effects of varieties of anti-Americanism on favorability of al-Qaeda. While the dislike of certain aspects of American culture generates sympathy toward al-Qaeda, anti-Americanism as a general attitude does not. More interestingly, dislike of American democracy, technology, and policy has either negative or no effect on favorable views of al-Qaeda. Literalist religious outlook generates positive views of al-Qaeda, but religiosity has a negative impact. These findings imply that we need to draw careful distinctions between politicized Islamic preferences and personal religiosity as well as the different types of anti-American sentiments in understanding Muslim political attitudes about terrorist groups.